The Sainte-Chapelle and the construction of sacral monarchy : royal architecture in thirteenth-century Paris - Cohen, Meredith (Cambridge University Press, 2015)
"This book offers a novel perspective on one of the most important monuments of French Gothic architecture, the Sainte-Chapelle, constructed in Paris by King Louis IX of France between 1239 and 1248 especially to hold and to celebrate Christ's Crown of Thorns. Meredith Cohen argues that the chapel's architecture, decoration, and use conveyed the notion of sacral kingship to its audience in Paris and in greater Europe, thereby implicitly elevating the French king to the level of suzerain, and establishing an early visual precedent for the political theories of royal sovereignty and French absolutism. By setting the chapel within its broader urban and royal contexts, this book offers new insight into royal representation and the rise of Paris as a political and cultural capital in the thirteenth century"--